Supportive release techniques provide no reintroduction benefit when efficacy and uptake is low. Issue 2 (21st March 2020) - Bannister, Hannah L.; Brandle, Robert; Delean, Steven; Paton, David C.; Moseby, Katherine E.
Abstract: Release methods can influence the outcome of reintroductions. We tested the effect of delayed, immediate and supplementary food/shelter release treatments on the reintroduction of brushtail possums Trichosurus vulpecula to an environment in which introduced predators, particularly foxes, were subject to control. Monitoring of 48 radio-collared possums over 3 months revealed that immediate release possums settled into a stable range significantly faster than other groups, but there were no differences in survival, dispersal distance, reproduction or body condition. Ten days after release possums from all treatment groups had lost body mass, but by day 60 most were heavier than at the time of translocation. After release, possums sometimes used shelter sites easily accessible to predators, but within 3 weeks they regularly selected safer shelter. Risky shelter selection and loss of condition immediately after release suggests that supplementary food and shelter could be beneficial, but supportive measures were rarely used or did not have the desired effect. In an environment with higher predator densities, risky shelter selection could lead to high post-release predation, and mass loss could encourage animals to forage in riskier ways, further increasing vulnerability. In these environments effective uptake of supplementary food and shelter could reduce predation risk, but supplementary measures would need to be presented in a way that maximises uptake. In contrast, if post-release predation risk is low then supportive measures may not be required. Innovative methods for providing post-release support should continue to be developed for reintroductions to areas where supportive measures are needed.